1998
DOI: 10.1149/1.1838606
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nanolithographic Concept Using Crack‐Assisted Patterning and Self‐Alignment Technology

Abstract: An original technology for fabricating nano-objects as small as several nanometers in width using a new class of lithographic masks is described. Glassy films such as Si02, SiN(H), and others deposited from vapor onto semiconductor substrates and capable of changing their volume and, hence, the internal stress during specific treatments, are used as a mask material. Using these film's features, a technology of mask formation is developed. Its originality consists of (i) making openings in the masks by controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
(6 reference statements)
0
15
2
Order By: Relevance
“…Through the study of SiNx thin film stress and refractive index, we found that there is a relationship between stress and refractive index. In low RF power, the stress increased and the refractive index improved too, but in high RF power, when the stress increased, the refractive index decreased contrarily, which is not similar to the report of Toivola and Gorokhov's [3,4] works using LPCVD.…”
Section: Figure 3 Refractive Index Of Sinx Film In Different Rf Powerscontrasting
confidence: 74%
“…Through the study of SiNx thin film stress and refractive index, we found that there is a relationship between stress and refractive index. In low RF power, the stress increased and the refractive index improved too, but in high RF power, when the stress increased, the refractive index decreased contrarily, which is not similar to the report of Toivola and Gorokhov's [3,4] works using LPCVD.…”
Section: Figure 3 Refractive Index Of Sinx Film In Different Rf Powerscontrasting
confidence: 74%
“…Formation of fine cracks at the periphery of the squares irradiated with laser pulses serves an indication for the growth of viscosity in the upper part of the bilayer structure. The formation process of such cracks is defined by two factors: (i) growth of the internal tensile stress in the film due to material compaction (the shrinkage of the film in the direction normal to the film plane does not completely eliminate the lateral internal tensile stress in the film) and (ii) growth of viscosity in the compacted layer due to increase of strength characteristics of the material proceeding with simultaneous vanishing of defects from the atomic network and with modification of the chemical composition of the layer (Gorokhov et al, 1998). As a result, quite a thick intermediate layer (up to ~50-80 nm), in which the insulator matrix has a variable chemical composition and altered structural, mechanical, physical and other material properties, forms during the reactions at the interface between the GeO2<Ge-NCs> heterolayer and the SiNxOy film.…”
Section: Geo2 Films Withmentioning
confidence: 99%
“…Other layers of germanium oxides, such as hexagonal GeO2 and GeO2<Ge-NCs> heterolayers, were unknown at that time when the possibility of using germanium oxide films in semiconductor industry was under evaluation. Also, there were no reported data on the interaction of layers of amorphous GeO2 with SiO2 or Si3N4 and on subsequent crystallisation of such binary compositions (Gorokhov et al, 1987(Gorokhov et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Gorokhov et al first comprehensively investigated cracking phenomena in various CVD processes as a novel cracking-assisted nanofabrication concept. 57 For example, a glassy, brittle layer such as a Si oxide (SiO 2 ) or Si nitride (Si 3 N 4 ) film was deposited on various substrates having different crystallographic orientations. As shown in Fig.…”
Section: Cvd-based Random Cracksmentioning
confidence: 99%
“…The damping layer generally possesses higher elastic and ductile characteristics (high fracture toughness) than the brittle thin film, so elastic and/or plastic deformation of the damper layer consumes the shear energy originating from crack propagation in the thin film. 35,57 Fig . 4A-iv shows orientation-free cracks in a SiO 2 film (450 nm thick, T d = 650°C) on a (111)oriented germanium (Ge) substrate with a viscous interlayer of germanium oxide (GeO 2 ).…”
Section: Cvd-based Random Cracksmentioning
confidence: 99%